Cotton crop: A situational analysis of Pakistan - Rana, Abdul Wajid; Ejaz, Amna; Shikoh, Sania Haider (International Food Policy Research Institute, 2020)
Cotton is the most important cash crop in Pakistan and cotton products export account for 55 percent of all foreign exchange earnings of the country. Nearly 26 percent of farmers grow cot-ton, and over 15 percent of total cultivated area is devoted to this crop, with production pri-marily in two provinces. Approximately 65 percent of Pakistan’s cotton is grown in Punjab, which has dry conditions, and the rest is grown in Sindh, which has a more humid climate, with negligible area under cotton in Khyber Pakhtunkhwa and Balochistan. Cotton production ac-counts for 4.5 percent of the value added in AgGDP and 0.8 per cent of GDP. It serves as the raw material for the textile industry, the country’s largest agro-industrial sector , employs 17 per-cent, earns 60 percent of foreign exchange and contributes 8.5 percent to GDP.